Distribuição da onça-pintada (carnivora: felidae) ao longo de uma paisagem antropizada: implicações para o manejo e conservação da espécie - Gregorini, Marina Zanin (2010)
We studied here the determinant factors of jaguar presence in a fragmented landscape, with implications to design and management of ecological corridors. In the first chapter, we evaluated the spatially structured effect of the natural preys’ richness on the jaguar occurrence and livestock depredation, as well as the vegetation cover influence on these processes. Our results show that jaguar occurrence is strongly determined by preys richness and the spatial component, showing that preys’ richness raises local quality and spatial aggregation acts in a positive way to this species. Otherwise, livestock predation, does not present a spatial component, being directly related to predator’s abundance. For the last, we highlight the absence of a vegetation cover effect on prey species richness and livestock depredation. In the second chapter, we test the effect of the area and isolation of natural fragments, agriculture intensity and spatial structure on jaguar presence. We verify that agriculture may represent a barrier to the jaguar dispersion and the presence of a larger natural fragment among other small patches increases the probability of jaguar presence. These results show that this species is efficient colonizing natural vegetation patches and the stepping stones can be used in conservation strategies to keep or reestablish connectivity in a landscape for the jaguar.